2013
DOI: 10.1108/jarhe-10-2012-0027
|View full text |Cite
|
Sign up to set email alerts
|

A (closer) look at collaboration using wikis

Abstract: Purpose -Wikis have been gaining attention in the practitioner and academic literature, suggesting their use as knowledge repositories in organizational environments and even as collaborative tools for reviewing scholarly publications. And yet, little is known about factors that foster or discourage use of this technology. The purpose of this paper is to take a closer look at collaboration using wikis. Design/methodology/approach -The authors look at an academic exercise using wikis in a college classroom to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Cinnamon et al (2010) write: "The frequent use of small groups in institutions of higher education is not surprising given the empirical and theoretical research that overwhelmingly supports the worth of active engagement for increased learning and development of higher-order cognitive skills" (p. 10). Furthermore, collaboration (what is called association in this section's subtitle) has been shown to be an aid to learning, insofar as social connections can motivate learners to learn (Hall and Buzwell, 2013;Hung and Yuen, 2010;King and Sen, 2013;Summers and Svinicki, 2007;Vasquez and Potter, 2013). Mauri et al (2014) have, likewise, shown collaborative writing to be positively associated with authentic learning.…”
Section: Learning By Doingmentioning
confidence: 96%
“…Cinnamon et al (2010) write: "The frequent use of small groups in institutions of higher education is not surprising given the empirical and theoretical research that overwhelmingly supports the worth of active engagement for increased learning and development of higher-order cognitive skills" (p. 10). Furthermore, collaboration (what is called association in this section's subtitle) has been shown to be an aid to learning, insofar as social connections can motivate learners to learn (Hall and Buzwell, 2013;Hung and Yuen, 2010;King and Sen, 2013;Summers and Svinicki, 2007;Vasquez and Potter, 2013). Mauri et al (2014) have, likewise, shown collaborative writing to be positively associated with authentic learning.…”
Section: Learning By Doingmentioning
confidence: 96%
“…A related concept is the perceived ease of use of an IS, which is considered the opposite of IS complexity (Thompson et al , 1991) and has been widely studied (Venkatesh and Bala, 2008). According to Vasquez and Potter (2013), “If perceiving a [wiki] technology as easy to use tends to foster adoption, then complexity will discourage users to adopt this technology” (p. 148).…”
Section: Hypothesis Developmentmentioning
confidence: 99%